Інтегроване інтелектуальне управління випарником та компресором у складі теплонасосної системи - Чайковська, Є. Є.; Стефанюк, В. В. (Видавництво Львівської політехніки, 2011)
Control provision by energy with heat pump on base of information as measure of the reflection of production and consumptions of the energy in correlation in united information.
Keywords: synergetic principle; expert system; control on decision-making level